DESIGN OF SHOCK ABSORBER TEST RIG USING MECHANICAL EXCITER TO DETERMINE TRANSMISSIBILITY AND NATURAL FREQUENCY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Shock absorber is a very key element in an automobile system, which is also an example of under damped vibration system. The aim of a Shock absorber is to absorb maximum shocks and vibrations in terms of kinetic energy and sometimes in terms of potential energy as well. Mechanical vibration exciters are necessary for modal testing of large components like, chassis, Shock absorbers. In this research, a shock absorber test rig using mechanical exciter has been developed for shock absorber testing and modal testing of Go-kart chassis. A Scotch-yoke mechanism is used for design of mechanical exciter. FEA software is used for static and modal analysis of exciter for determining natural frequency and FFT analyzer to determine the transmissibility of shock absorber. Also to validate the results obtained from FFT analyzer FEA software is used. Natural frequency of exciter is mainly depends on its mass and stiffness properties. The results of natural frequency and mode shapes are obtained from FEA software. The results obtained from the FFT analyzer will in the form of a waveform which is used to find out the transmissibility at various loads and speeds. The natural frequency of mechanical exciter is obtained from FEA software. Further, the FEA and experimental results of Transmissibility and natural frequency of mechanical exciter are compared for necessary corrections in design parameters of the shock absorber behavior and chassis.